A2_4 Doing Whatever a Spider Can - Forster, James; Bryan, Mark; Stone, Alex (Physics Special Topics, 2012)
In Spiderman 2 there is a scene in which Spiderman stops a runaway train using his webbing to provide a counter-force. Using the information available this paper examines the material properties of the webbing under these conditions and finds the Young's modulus to be 3.12GPa, a reasonable value for spider silk.